Football in Częstochowa in the years 1919-1927 - Krzysztof Kościański (Jan Długosz University in Częstochowa, 2020)
After Poland regained its independence, Częstochowa was one of the largest cities in terms of population. In relation to football, it was treated as a province, and the sport discipline itself was just developing. The stadiums were created as well as the 1st Stadium dedicated to football, which influenced the dissemination of this discipline. The number of clubs with the football section increased every year. In 1923, two clubs from Częstochowa and one from Raków formed the Częstochowa 'C' division, performing under the auspices of the Krakow Regional Sports Association. Four years later, there were already two groups of fourteen teams in genral. Teams from Częstochowa competed under patronage of Sosnowiec Subdistrict Football Association. Between 1919-1927 neither of teams from Częstochowa got promoted to division "A". In the year 1927 Częstochowa Sub-District Football Association was established, whose functioning had a significant impact on the further development of football in Częstochowa. In that period of time the best teams were: Częstochowa Sports Club, "Victoria 1922" Częstochowa Sports Club, Sports Club Czestochowa and Sports Club "Warta" Czestochowa.